A NEW LATE MIOCENE PLANT ASSEMBLAGE FROM MESSARA BASIN (CRETE, GREECE) - Zidianakis G., Zidianakis G.; Iliopoulos, G.; Fassoulas, C. (Bulletin of the Geological Society of Greece, 2010)
A rich terrigenous plant assemblage was recently excavated from early Tortonian deposits at Messara basin, southern Crete. The macro-remains are perfectly preserved as impressions or carbonized compressions in poorly lithified and locally laminated, blue-green clays with an age of at least 10.5 Ma and thus can be considered as the oldest plant assemblage found in Crete todate. Gymnosperms are represented by the families of Pinaceae (pine needles and winged seeds), Cupressaceae and Taxodiaceae (leafy twings of Taxodium). Besides, 19 different angiosperm taxa of trees and shrubs have been also determined. Fagaceae is the most diversified with foliage of beech and several deciduous and evergreen oaks, while Myricaceae contribute mainly as abundant leaf remains of Myrica lignitum. Accessory elements of evergreen Lauraceae (Daphnogene polymorpha), sclerophyllus shrubs of Buxaceae (Buxus pliocenica) and various deciduous dicotyledonous such as Populus crenata, Liquidambar europaea, Carya minor and Acer pseudomonspessulanum are well documented. Leguminosae is recorded by a significant number of various small leaflet imprints. Therefore, the recovered remains indicate swampy forest habitats dominated by hygrophilic woody plants of Taxodium and Myrica, while in the surrounding plains and slopes a mixed mesophytic forest with a relatively low proportion of evergreen plants occurred in early-Late Miocene times in Crete depicting a moderately humid, warm-temperate nature for the climate.